Building an Ethos of Poetry Pedagogy among Pre-service Teachers through Mock Lesson Experiences within the Poetry-Teaching (POT) Framework: Metrophobia or Metrophilia? - Şakire Erbay Çetinkaya (Universitas Hamzanwadi, 2025)
Despite the documented potential of poetry for emotional and personal development and expression in foreign language instruction, the genre is the least popular one. The side-lined nature of poetry pedagogy in English language instruction necessitates further studies exploring its systematic integration to revitalise it. The current case study is part of a larger-scale project on concrete teaching experiences, reflections, insights, new learnings, and realisations, as well as future intentions, of a convenience sample of 39 third-grade pre-service teachers (F=24; M=15). They conducted mock lessons within the six-stage Poetry Teaching Framework (POT) in a two-term required methodology course. POT initially covers six stages, namely, Tune-in, Basic Comprehension, Detailed Analysis, Cultivation, Bridge, and Reflection. The current case study partially focused on participants’ possible evolution from metrophobia to metrophilia, namely love for poetry, as well as perceptions. The qualitative data were gathered with a final self-report in the form of an open-ended questionnaire, for such self-administered tools could offer the participants the freedom of expression, thereby resulting in in-depth and authentic data. The process was reported to transform pre-service teachers’ existing indifference to poetry. Despite their emerging positivity, cautious and conditional optimism was tracked for several challenges, including complex and archaic language, irrelevance to curricular objectives, lack of teacher interest and related knowledge, perceived risk of resulting in student boredom, the challenging nature of the POT, and lack of real teaching experience. To alleviate teacher metrophobia, the study concludes with suggestions in line with the findings of the current research for pre-service teacher educators.